Development and application of lean product development performance measurement tool. Issue 3 (3rd March 2016) - Al-Ashaab, Ahmed; Golob, Matic; Urrutia, Usue Aliende; Gourdin, Mathilde; Petritsch, Christoph; Summers, Mark; El-Nounu, Abdulrahman
Abstract : The need of applying lean thinking to product development is becoming a must for the organisations to succeed in the current industry. This paper presents the development and application of a tool that helps to identify the actual status of the organisation in relation to the lean principles. Overview of the literature highlighted the need of developing a tool focused on assessing the implementation of lean principles themselves, rather than quantitative metrics. Based on the idea of the balanced scorecard, four perspectives, with their corresponding set of questions, were defined reflecting the enablers of the lean product development model proposed by the Lean Product and Process Development European project. A five-level scale was customised to reflect different readiness levels of lean implementation. The tool was used in case studies in two organisations; first in aerospace and second in automotive. Examples of measurement from two different organisations demonstrated the accuracy of the tool in assessing and defining the starting conditions for adapting lean principles and practices.